Systematic review: clinical characteristics of anti-N-methyl-D-aspartate receptor encephalitis - Zhao, Xi; Teng, Yuou; Ni, Jingnian; Li, Ting; Shi, Jing; Wei, Mingqing (Frontiers in Human Neuroscience, 2023)
The number of reported cases of anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis has gradually increased since its discovery in 2007, while there are no uniform treatment guidelines.: To summarize the clinical characteristics of patients with anti-NMDAR encephalitis and to analyze the factors affecting the disease prognosis. Methods: A systematic analysis of medical records was conducted, and PubMed, Embase, and Cochrane Library were searched from January 1, 2011, to December 31, 2021. Data were extracted, analyzed, and recorded in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Results: This study included 472 case reports. Most patients had prodromal symptoms of about two weeks, including psychiatric symptoms (53.2%), flu-like symptoms (51.5%), and seizures (23.9%), among others. Poor prognoses were associated with patients who had autonomic instability (P=0.010), central hypoventilation (P=0.014), and ICU support (P=0.002). Patients with a higher age of onset were more likely to develop central hypoventilation (OR 1.024, CI 1.006-1.042, P=0.009), cognitive impairment (OR 1.023, CI 1.009-1.037, P=0.001), and memory impairment (OR 1.034, CI 1.017-1.050, P＜0.001), whereas patients with a lower age were more likely to have seizures (OR 0.979, CI 0.965-0.993, P=0.003). In this study, 97.0% of patients received immunotherapy, with the most commonly used treatment regimen being intravenous methylprednisolone (IVGC) and intravenous immunoglobulin (IVIG). When compared with other treatment regimens, the IVGC+IVIG regimen (P＜0.001) resulted in better prognoses. Conclusion: When encountering patients with fever, headache, and initial psychiatric symptoms of unknown etiology, clinicians should test their CSF for antibodies to distinguish autoimmune encephalitis. Patients with autonomic instability, central hypoventilation, and ICU support had poorer prognoses. Clinicians should be aware that older patients are more likely to develop central hypoventilation, cognitive impairment, and memory impairment, while younger patients are more likely to develop seizures. The IVGC+IVIG treatment regimen has better prognoses than others. This study includes case reports, which have obvious selection bias, and there are no unified standards to measure the severity of the disease. Therefore, in the future, larger samples and randomized controlled trials are needed to evaluate the efficacy of different treatment regimens.